2021
DOI: 10.1620/tjem.254.155
|View full text |Cite
|
Sign up to set email alerts
|

High Feasibility and Safety, but Negligible Efficacy of Acupressure for Treating Nausea in Cancer Patients Admitted to the Palliative Care Unit: A Pilot Study

Abstract: Management of nausea is an important dimension of palliative care. The first choice for treating nausea is antiemetics, but their efficacy is inadequate. Acupressure intervention for nausea in cancer patients has been studied as a non-pharmacological therapy, and appears to have had some effect. However, such a therapy has not been well reviewed in patients with terminal cancer. The purpose of this study was to clarify the feasibility of acupressure intervention and examine its safety and preliminary efficacy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
2
0
0
Order By: Relevance
“…Likewise, multiple studies have shown that auricular acupressure (AA) can effectively reduce the incidence and severity of acute CINV in patients with breast cancer [ 22 , 23 ]. Together, our study strengthens the previous notion [ [4] , [5] , [6] , [11] , [12] , [13] , [14] , [15] , [16] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] ] (15/20 studies show a positive impact of acupressure on reducing nausea in patients with cancer, listed in Table 5 ) that acupressure at P6 and/or ST36 are effective in reducing acute CIN for breast cancer patients. Despite a positive finding, it is important to note that several reports indicate that acupressure may not be effective in relieving CINV ( Table 5 ) [ 4 , 13 , 24 , 29 , 32 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Likewise, multiple studies have shown that auricular acupressure (AA) can effectively reduce the incidence and severity of acute CINV in patients with breast cancer [ 22 , 23 ]. Together, our study strengthens the previous notion [ [4] , [5] , [6] , [11] , [12] , [13] , [14] , [15] , [16] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] ] (15/20 studies show a positive impact of acupressure on reducing nausea in patients with cancer, listed in Table 5 ) that acupressure at P6 and/or ST36 are effective in reducing acute CIN for breast cancer patients. Despite a positive finding, it is important to note that several reports indicate that acupressure may not be effective in relieving CINV ( Table 5 ) [ 4 , 13 , 24 , 29 , 32 ].…”
Section: Resultssupporting
confidence: 92%
“…Together, our study strengthens the previous notion [ [4] , [5] , [6] , [11] , [12] , [13] , [14] , [15] , [16] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] ] (15/20 studies show a positive impact of acupressure on reducing nausea in patients with cancer, listed in Table 5 ) that acupressure at P6 and/or ST36 are effective in reducing acute CIN for breast cancer patients. Despite a positive finding, it is important to note that several reports indicate that acupressure may not be effective in relieving CINV ( Table 5 ) [ 4 , 13 , 24 , 29 , 32 ]. However, it is crucial to consider that these studies often recruited non-homogeneous subsets of participants who may have varied responses to acupressure treatments and thus influence the overall findings of the study.…”
Section: Resultssupporting
confidence: 92%
“…After removing the duplicate articles, we reviewed the titles and abstracts of 4,273 articles. This resulted in 58 articles being eligible for full-text review, of which 10 met the selection criteria [22][23][24][25][26][27][28][29][30][31]. The agreement rate between the reviewers was 82.8% (48/58).…”
Section: Resultsmentioning
confidence: 99%
“…CINV masih memiliki dampak yang tinggi pada berbagai aspek kualitas hidup (Ilyas et al, 2020). Keadaan mual muntah yang tidak terkendali dapat menyebabkan ketidakseimbangan cairan elektrolit, dehidrasi, anoreksia dan penurunan berat badan (Tsugita et al, 2021).…”
unclassified